Lex RUKI in Baltic in perspective of the early Baltic loans in Finnic - Blažek, Václav; Šefčík, Ondřej (Baltistica, 2022)
This discourse puts forward arguments for the complete validity of Pedersen’s Law, also called ‘Lex RUKI’, in Proto-Baltic (or an early Baltic dialect) in all positions. This conclusion was formulated based on an analysis of the early Baltic borrowings into Finnic.